MINAPOLITAN AREA DEVELOPMENT STRATEGY IN OGAN KOMERING ULU REGENCY - Trimurti Handayani; Yunita Sari; Fifian, Fifian Permata Sari; Anggi Fatmayati; Dadang Kurnia (International Journal of Social Science, 2022)
This study aims to identify the internal and external factors involved in the development of the minapolitan area, as well as to analyze the development strategy of the minapolitan area in Ogan Komering Ulu Regency. This research was conducted using the SWOT analysis method (Strengths, Weaknesses, Opportunities, Threats). The results of this study indicate that the internal factors in this study are the availability of abundant water, the existence of the Raksa Jiwa fish seed center (BBI), the availability of labor, and the availability of own land. While the internal factors that become weaknesses are not being able to make their own feed, low community motivation, lack of capital support, low skills of fish farmers, lack of socialization from the government. External factors that become opportunities are government regulations regarding the determination of the minapolitan area of ​​OKU Regency and the potential for higher demand for fish. Meanwhile, external factors that pose a threat are the high price of feed, and the presence of competitors from other regions. The results of the SWOT analysis show that alternative strategies that can be implemented include maximizing the potential of the available resources, optimizing the role of the Raksa Jiwa Fish Seed Center (BBI), optimizing the planning for the use of natural resources by compiling a master plan for the minapolitan area.